Komunikasi Empati dalam Pelayanan Masyarakat - Nora Zulvianti (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2012)
Our lives can not be separated from the communication. Then the society existence it self also can not be separated with communication. Every one starting from the main organization like our family, communities and the state as the largest organization for a nation, all require communication. In the provision of services to the community (public) holds the crucial role of communication clear. This article outlines not only communication but more general role of communication empathi specializes in providing services to the public.